Effects of mirror therapy in post-traumatic complex regional pain syndrome type-1: a randomized controlled study - Özdemir, Elif Can; Elhan, Atilla H.; Küçükdeveci, Ayşe A. (Journal of rehabilitation medicine, 2024)
Objective: To investigate the effects of mirror therapy applied in addition to routine rehabilitation on clinical outcomes in post-traumatic complex regional pain syndrome type 1. Design: Single-blind randomized controlled trial. Subjects: Patients with trauma-induced complex regional pain syndrome type 1 of the hand receiving outpatient rehabilitation. Methods: Patients were randomized into mirror therapy and control groups. All patients received routine physical therapy and rehabilitation for 20 sessions (5 sessions/week, for 4 weeks). The mirror group received additional mirror therapy at each session. The primary outcome was pain intensity by numeric rating scale. Secondary outcomes were grip/pinch strength, hand/wrist circumference, dexterity, hand activities, and health-related quality of life. All assessments were performed before and immediately after the treatment, and 4 weeks later at follow-up. Results: Forty patients were enrolled, 20 in each group. Both groups revealed statistically significant improvements from therapy regarding pain, grip/pinch strength, wrist circumference, dexterity, and hand activities (p <  0.05). When groups were compared regarding the improvements in assessment parameters, no statistically significant difference was found between the 2 groups in any of the outcomes (p > 0.05). Conclusion: Mirror therapy applied in addition to routine therapy in post-traumatic complex regional pain syndrome type 1 did not provide extra benefit to the improvement of pain, function, and other clinical outcomes.